Development and Validation of a Novel Prognostic Nomogram Combined With Desmoplastic Reaction for Synchronous Colorectal Peritoneal Metastasis - Qin, Xiusen; Zhao, Mingpeng; Deng, Weihao; Huang, Yan; Cheng, Zhiqiang; Chung, Jacqueline Pui Wah; Chen, Xufei; Yang, Keli; Chan, David Yiu Leung; Wang, Hui (Frontiers in Oncology, 2022)
Purpose The prognostic value of desmoplastic reaction (DR) has not been investigated in colorectal cancer (CRC) patients with synchronous peritoneal metastasis (SPM). The present study aimed to identify whether DR can predict overall survival (OS) and develop a novel prognostic nomogram. Methods CRC Patients with SPM were enrolled from a single center between July 2007 and July 2019. DR patterns in primary tumors were classified as mature, intermediate, or immature according to the existence and absence of keloid-like collagen or myxoid stroma. COX regression analysis was used to identify independent factors associated with OS and a nomogram was developed subsequently. Results 198 patients and 99 patients were randomly allocated into the training and validation groups. The median OS in the training group was 36, 25, and 12 months in mature, intermediate, and immature DR categories, respectively. Age, T stage, extraperitoneal metastasis, differentiation, cytoreductive surgery (CRS), hyperthermic intraperitoneal chemotherapy (HIPEC), and DR categorization were independent variables for OS, based on which the nomogram was developed. The C-index of the nomogram in the training and validation group was 0.773 (95% CI 0.734-0.812) and 0.767 (95% CI 0.708-0.826). The calibration plots showed satisfactory agreement between the actual outcome and nomogram-predicted OS probabilities in the training and validation cohorts. Conclusions DR classification in the primary tumor is a potential prognostic index for CRC patients with SPM. The novel prognostic nomogram combined with DR classification has good discrimination and accuracy in predicting the OS for CRC patients with SPM.